2015
DOI: 10.1111/resp.12515
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic link between tuberculosis and cigarette/biomass smoke exposure: Limitations despite the vast literature

Abstract: The geographic overlap between the prevalence of cigarette smoke (CS) exposure and tuberculosis (TB) in the world is striking. In recent years, relatively large number of studies has linked cigarette or biomass fuel smoke exposure and various aspects of TB. Our goals are to summarize the significance of the known published studies, graphically represent reports that quantified the association and discuss their potential limitations. PubMed searches were performed using the key words 'tuberculosis' with 'cigare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 71 publications
(215 reference statements)
1
24
0
Order By: Relevance
“…Uncertainty therefore remains about the rate and drivers of recovery/deterioration in those with post-TB lung damage. Factors influencing the progression of lung damage may include modifiable exposures such as smoking, biomass fuel[ 69 , 70 ], and ongoing respiratory tract infections[ 71 ]. Further research in this area may inform strategies to prevent decline in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Uncertainty therefore remains about the rate and drivers of recovery/deterioration in those with post-TB lung damage. Factors influencing the progression of lung damage may include modifiable exposures such as smoking, biomass fuel[ 69 , 70 ], and ongoing respiratory tract infections[ 71 ]. Further research in this area may inform strategies to prevent decline in this group.…”
Section: Discussionmentioning
confidence: 99%
“…63 Moreover, some studies reported an association between tuberculosis cases and biomass fuel smoke exposure compared with exposure to cleaner forms of fuels. 64 Despite the link between chronic exposure to BS and the occurrence of respiratory infections being based primarily on epidemiological data, few experimental studies in animals have reinforced this idea. Thus, Hatch et al showed a significantly increased mortality on mice with streptococcal pulmonary infection instilled with carbonaceous particles.…”
Section: Bs Alters Pulmonary Host Defense Mechanismsmentioning
confidence: 99%
“…It is noteworthy that countries with a high incidence of TB tend to also have an elevated proportion of smokers [3]. The link between TB and cigarette smoke has already been suggested since 1918 and it has been confirmed by several epidemiological studies [4,5]. There is evidence that cigarette smoke is a risk factor for TB, aiding the infection, the progression to the active disease and the severity of the illness [6,7].…”
Section: Introductionmentioning
confidence: 87%